MANAJEMEN KOMUNIKASI KRISIS HUMAS PT PLN UID S2JB DALAM MENGELOLA ISU KECELAKAAN LISTRIK DI KOTA PALEMBANG - Putri Wulandari; Ahmad Muhaimin; Sonia Nurprameswari (AT-TAWASUL, 2026)
Electrical accidents can cause public concern and affect public trust in an organization. Therefore, PT PLN UID S2JB requires appropriate crisis communication and post-crisis communication strategies in managing electrical accident issues in Palembang City. This study aims to determine the crisis communication management and post-crisis communication of PT PLN UID S2JB Public Relations in managing electrical accident issues and restoring public trust in Palembang City. This study used a descriptive qualitative method with data collection techniques through interviews, observations, and documentation. The analysis was conducted using the Situational Crisis Communication Theory (SCCT) develoved by W. Timothy Coombs (2007), which explains organizational communication strategies based on the level of crisis responsibility attribution. The results showed that PT PLN UID S2JB identified issues through information verification and cross-department coordination to determine the severity level of incidents and the form of communication responses to the public. Message preparation was carried out using an educational approach with simple, persuasive language adjusted to community conditions. Communication dissemination was conducted through social media, mass media, and face-to-face socialization, while communication monitoring was carried out through online media monitoring and public responses to electrical accident issues. In post-crisis communication, PT PLN UID S2JB restored public trust through empathetic approaches, safety education, information transparency, and preventive actions. However, the implementation of safety education was still uneven, and the measurement of post